Parents Perceptions of Online Learning Videos Physical Education and Sports Health In State Elementary School - Rahmadi Rahmadi; Syamsul Arifin; M. Sultan Almalik (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This study aims to determine the parents' perception of the learning videos of physical education subjects given by the teacher to students in carrying out the teaching and learning process. This study uses quantitative research methods. The type of research used is survey research with data collection techniques in the form of a google form questionnaire. The sample of this study was the parents of students at SD Negeri 1 Landasan Ulin Utara, Banjarbaru City who were willing to fill out questionnaires from class V and III, obtained 113 respondent data. The data analysis technique used descriptive statistics which were presented using frequency and percentage tables. The results of this study indicate that the parents' perception of the learning video is quite good, it can be seen from the data of eight indicators, there are four indicators that are classified as good category (50%), and four indicators are classified as moderate category (50%).